The sustainability of meat and cured meats in Italy: Nutritional aspect, food safety, environmental impact, animal welfare, circular economy, fight against waste - Ettore Capri; Giuseppe Pulina; Elisabetta Bernardi (FrancoAngeli, 2019)
From the mid-1980s, meat consumption in Italy and the western world have stabilised and, in the face of a well-established food security, we have witnessed a changed sensitivity for ethical issues, such as animal welfare and environmental impacts of farms. The challenge of livestock production has therefore become that of "producing more with less resources", a challenge at the base of the circular economy, which sets itself the goal of a greater offer, but more "sustainable", efficient, attentive to the environment and animal welfare, to the fair remuneration of breeders and all those who participate in the creation of value in Italian supply chains. Analysing the sustainability of meat and cured meats means studying in the most objective way possible different topics concerning both the consumer and the livestock production. This volume presents an interdisciplinary study to describe the "5 faces" of meat sustainability, represented by as many chapters: nutrition, environmental impacts and the circular economy applied to farms and industry, food security and animal welfare, the economic aspects of supply chains and the fight against food waste.
Keywords: 300; meat consumption; sustainability; nutrition; food safety; environmental impact; animal welfare